Analyzing the Students’ Speaking Skills Through Telling Folklore in the English Classroom - Daeli, Tuti Ardianti; Harefa, Afore Tahir; Maruao, Nursayani; Harefa, Trisman (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to examine the effectiveness of using folktales in improving the English speaking skills of students in class VIII of SMPN 1 Gunungsitoli Barat. Using a descriptive qualitative approach, this study involved 26 students as the main subjects. The results showed that the integration of folktales in learning had a significant impact on students' pronunciation ability, where 60% of them achieved a good score. Folklore not only improves pronunciation, but also eases the teaching and assessment process, and fosters students' interest in learning. Supporting factors such as the use of varied teaching methods and students' interest in local culture also catalysed the success. Comparative analysis showed that students who were active in folklore-based activities had higher levels of fluency and confidence than the less engaged group. However, the study also identified a number of challenges, such as limited learning time and limited available resources, which require further attention. In conclusion, folklore proved to be an effective learning medium in improving students' English speaking skills. In addition, it made a positive contribution to overall learning, by strengthening students' appreciation of local culture while improving the quality of the teaching and learning process.